TRACING THE LEGACY: COMPARING MARY SHELLEY’S FRANKENSTEIN TO JENNIFER MCMAHON’S THE CHILDREN ON THE HILL - Sa'adah, Sufi Ikrima; Rochmah, Maulidya; Nuristama, Ramadhina Ulfa (ELite Journal : International Journal of Education, Language and Literature, 2023)
Mary Shelley’s Frankenstein has become a prominent predecessor for abundant adaptations in popular culture. Although the novel was published more than two hundred years ago, numerous writers have made it their most reference and inspiration. This article aims to investigate the traces Frankenstein has left on Jennifer McMahon’s The Children on the Hill under the argument that the former has served as the source for the latter. Therefore, this research belongs to the literary influence study. Drawing the analysis under the compare and contrast method, this study results in some parts of Frankenstein that are recreated in The Children on the Hill. Those parts include the description of the creator’s life, the trigger of the creation, the creation’s process, and its horrible consequences. The result also shows that McMahon’s book presents the recreated parts in a more horrifying way, especially about the details of the experiment and the shocking ending when the monster kidnaps many female adolescents to turn them into monsters like her. This study concludes that a monster does not always come in a hideous appearance like what Victor created. However, the monster can also lie dormant within a human’s personality, which can bring about terrible destruction when it comes out.